Systemic mastocytosis with associated acute myeloid leukemia with t (8; 21) (q22; q22) - V S Gadage; P S Kadam Amare; K S Galani; N Mittal (Wolters Kluwer Medknow Publications, 2012)
Systemic mastocytosis with associated clonal hematological nonmast cell lineage disease (SM-AHNMD) is a subtype of mastocytosis associated commonly with myeloid neoplasms, Non-Hodgkin's lymphoma, or other hematological neoplasms. In these conditions, mastocytosis needs to be differentiated from mast cell hyperplasia or mast cell activation states. Neoplastic nature of mastocytosis is proved either by morphology, aberrant immunophenotype, or detection of point mutation at codon-816 of c-kit gene. This is a rare entity, even more so in pediatric population. Herein, we report a case of 14-year-old girl with SM associated with acute myeloid leukemia with maturation with t(8;21). Multifocal dense infiltrate of spindle-shaped mast cells on bone marrow aspirate and biopsy with coexpression of CD2 and CD25 by flow cytometric analysis proved the SM component at the time of diagnosis and persistence at post induction status also.